Effect of various nutrient sources on productivity and economics of groundnut (Arachis hypogaea L.) - Ram, Chatra; Singh, H.B.; Patel, R.B.; Singh, Hanuman; Kumar, Gopal (Annals of Agricultural Research, 2014)
Short Note